(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: T2DM is a condition that should not be eliminated but can be self-managed to maintain the glucose levels in the blood stable and optimal to prevent complications (Choi et al., 2017). As evidenced, health education is one of the important factors that may help the patient about patient knowledge, attitude and management of diabetes. The objective of the current paper was to assess the impact of health education on health perception and knowledge, attitudes, and glycemic control in T2DM patients. Objective: The purpose of the research was to determine how organized health education programs affect patient knowledge about diabetes, their attitude towards diabetes management and glycemic control. Methods: pre- post intervention was employed, in which 258 T2DM patients were outpatients. The respondents underwent a 4-week health education program, in terms of diet management, physical exercises, medication, and self-blood glucose monitoring. The data were represented in the structured questionnaires, which were completed before and after the intervention considering the levels of knowledge, attitudes, and the glycemic control also referred to as the HbA1c levels. To analyze the data, statistical tests included Shapiro-Wilk normality test, Cronbach alpha to measure the reliability, One-way ANOVA, Independent Samples t-test, Krushal-Wallis Test, Chi-Square test, Pearson and regression analysis. Results: The researchers were able to create a good example in the increase in knowledge and attitude to the management of diabetes following health education. Requested attendance at health education was associated with better glycemic control as demonstrated by the substantial decreases in the levels of HbA1c. The results of independent Samples t-test and ANOVA were used to show that the difference in the knowledge between the males and females and older and younger individuals is significant and Chi-Square Test was used to show that there is a strong correlation between the attendance to the health education programs and the glycemic control. Regarding Pearson correlation analysis, the more people were well-informed the easier it was to control their glycemia. The regression analysis indicated that knowledge and glycemic control were positively correlated although it only outlined a small fraction of the variance in the glycemic outcomes. Conclusions: Health education interventions have a significant impact on increasing the level of knowledge, attitudes, and glycemic control, among T2DM patients. The results affirm that age, gender, and age-specific health education on health literacy had a significant role. Despite the importance related to the knowledge in glycemic management, it must be combined with multifaceted model of medication adherence, lifestyle and psychosocial support that may be important in enabling an individual to manage diabetes.